2017
DOI: 10.1007/s12011-017-1032-0
|View full text |Cite
|
Sign up to set email alerts
|

Hair Trace Element and Electrolyte Content in Women with Natural and In Vitro Fertilization-Induced Pregnancy

Abstract: The objective of the present study was to perform comparative analysis of hair trace element content in women with natural and in vitro fertilization (IVF)-induced pregnancy. Hair trace element content in 33 women with IVF-induced pregnancy and 99 age- and body mass index-matched control pregnant women (natural pregnancy) was assessed using inductively coupled plasma mass spectrometry. The results demonstrated that IVF-pregnant women are characterized by significantly lower hair levels of Cu, Fe, Si, Zn, Ca, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…In a study to examine the heavy metals and metalloids status in hair samples of women with IVF pregnancy and their 9-month-old children, Skalny et al ( 29 ) found out that women with IVF pregnancy demonstrated significantly high hair As, Hg, Li levels and their children also had significantly elevated hair Hg and Mo concentrations compared to control ( 30 ). Similarly, another case-control study by Skalny et al ( 30 ) demonstrated that IVF pregnancy correlated significantly with elevated hair levels of As ( p < 0.05) suggestive of arsenic overload in IVF patients ( 31 ). Garcia-Fortea et al ( 28 ) in a prospective cohort study examined 194 women undergoing IVF and found an inverse correlation between concentration of Hg in hair and probability of mature oocytes (RR = 0.81, 95% CI: 0.70–0.95) while a direct association was demonstrated with Pb (RR = 1.18, 95% CI: 1.03–1.35) ( 29 ).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In a study to examine the heavy metals and metalloids status in hair samples of women with IVF pregnancy and their 9-month-old children, Skalny et al ( 29 ) found out that women with IVF pregnancy demonstrated significantly high hair As, Hg, Li levels and their children also had significantly elevated hair Hg and Mo concentrations compared to control ( 30 ). Similarly, another case-control study by Skalny et al ( 30 ) demonstrated that IVF pregnancy correlated significantly with elevated hair levels of As ( p < 0.05) suggestive of arsenic overload in IVF patients ( 31 ). Garcia-Fortea et al ( 28 ) in a prospective cohort study examined 194 women undergoing IVF and found an inverse correlation between concentration of Hg in hair and probability of mature oocytes (RR = 0.81, 95% CI: 0.70–0.95) while a direct association was demonstrated with Pb (RR = 1.18, 95% CI: 1.03–1.35) ( 29 ).…”
Section: Discussionmentioning
confidence: 81%
“…A study by Wu et al ( 32 ) revealed an inverse association between serum Cr level of IVF patients with the count of mature oocytes ( p = 0.033), in addition, arsenic (As) concentration in female serum were inversely associated with the probabilities to obtain good-quality cleavage embryos ( p < 0.01) ( 33 ). On the other hand, Tulic et al ( 31 ) found a significant negative correlation between IVF outcome with higher serum concentrations of Pb ( p = 0.046) and Cd ( p = 0.012) ( 32 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, Sr has been proved to stimulate the osteogenic differentiation of MSCs by up-regulating extracellular matrix (ECM) gene expression and activating Wnt/β-catenin pathway 53 . It was also reported that Si stimulated MSCs differentiation by activating Wnt pathways 54 , 55 . Hence, it is reasonable to speculate that in this study, Sr and Si ions released from SPS bioactive scaffold may together contribute to promote subchondral bone regeneration via activation of the Wnt pathway.…”
Section: Discussionmentioning
confidence: 91%
“…A large number of studies have shown that Se prevents the oxidative stress induced by some mycotoxins 36 – 38 . In this study, the levels of MDA and H 2 O 2 were significantly lower in the groups SD1–4 than in the groups D1–4 ( P < 0.05 or P < 0.01), and the activities of SOD and CAT, the levels of GSH, T-AOC, and the capacity of the cells to inhibit hydroxyl radicals were higher in the groups SD1–4 than in the groups D1–4 mostly ( P < 0.05 or P < 0.01).…”
Section: Discussionmentioning
confidence: 99%